2020
DOI: 10.3390/nu12082291
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Health-Promoting Attributes of Plant Proteins as a Functional Ingredient for the Food Sector: A Systematic Review of Human Interventional Studies

Abstract: The potential beneficial effects of plant-based diets on human health have been extensively studied. However, the evidence regarding the health effects of extracted plant-based proteins as functional ingredients, other than soya, is scarce. The aim of this review was to compile evidence on the effects of extracted protein from a wide range of traditional and novel plant sources on glycemic responses, appetite, body weight, metabolic, cardiovascular and muscle health. A comprehensive search of PubMed, EMBASE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 79 publications
(177 reference statements)
0
20
0
Order By: Relevance
“…Consuming the recommended quantity of good-quality protein is essential for optimal human growth, development, and health (G. Wu, 2016). The effects of plant proteins, including legumes (peas, lupine, fava beans, and lentils), have recently been reviewed, confirming the health-promoting effects of these extracts on glycemic, appetite, cardiovascular, and muscular outcomes (Lonnie et al, 2020). The benefits of technological treatment of these protein sources to remove ANFs have already been stated.…”
Section: Health Effects Of the Technologically Obtained Pismentioning
confidence: 99%
“…Consuming the recommended quantity of good-quality protein is essential for optimal human growth, development, and health (G. Wu, 2016). The effects of plant proteins, including legumes (peas, lupine, fava beans, and lentils), have recently been reviewed, confirming the health-promoting effects of these extracts on glycemic, appetite, cardiovascular, and muscular outcomes (Lonnie et al, 2020). The benefits of technological treatment of these protein sources to remove ANFs have already been stated.…”
Section: Health Effects Of the Technologically Obtained Pismentioning
confidence: 99%
“…Studies have shown that the addition of pea protein to gluten‐free muffins has the same properties comparable to muffins made from wheat; it also ensures adequate amounts of essential amino acids such as lysine in the human diet (Xu et al ., 2020; Lu et al ., 2019). Besides, pea protein, lupin protein, fava bean protein and lentil protein also have positive health effects on glycaemic control in humans (Lonnie et al ., 2020). Furthermore, adding pea protein to low‐moisture ERPs can significantly reduce glucose release, and its products also have good performance (Beck et al ., 2018).…”
Section: Effects Of Adding Whole Legumes Flour On the Quality And Gi ...mentioning
confidence: 99%
“…Quinoa oil is high in omega-6 and vitamin E content. Quinoa starch is used in many innovative industrial applications due to its functional properties, including the stability of its structure during freezing and the modification of solution viscosities [ 127 ].…”
Section: Unconventional and Alternative Sources Of Proteinsmentioning
confidence: 99%